Kajian Literatur Perikanan: Analisis Faktor-Faktor yang dapat Mempengaruhi Produktivitas Budidaya Ikan Lele Dumbo di Indonesia - Samara, Anugerah; Liubana, Debora Victoria; Husnawati, Dewi; Nomleni, Aryok (Universitas Batangahari Jambi, 2026)
Catfish farming of African catfish (Clarias gariepinus) is one of the leading freshwater aquaculture commodities in Indonesia with strong economic potential. However, its productivity is influenced not only by biological characteristics but also by various interrelated external factors. This study aims to analyze the factors affecting the productivity of African catfish farming using a literature review approach. Data were collected from national scientific sources published between 2015 and 2025, including journal articles, research reports, and conference proceedings. The results indicate that technical factors such as seed quality, feed management, stocking density, and water quality play a significant role in determining productivity. In addition, socio-economic factors, including farmers’ experience, education level, and access to training, also influence farming performance. Institutional support, access to technology, environmental conditions, and market price fluctuations are additional important determinants